2014
DOI: 10.1016/j.jphys.2014.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapists demonstrate weight stigma: a cross-sectional survey of Australian physiotherapists

Abstract: Physiotherapists demonstrate weight stigma. This finding is likely to affect the way they communicate with patients about their weight, which may negatively impact their patients. It is recommended that physiotherapists reflect on their own attitudes towards people who are overweight and whether weight stigma influences treatment focus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
65
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 42 publications
3
65
0
5
Order By: Relevance
“…However, this theory cannot explain why only some people stigmatise. It cannot explain why some physiotherapists score highly on weight stigma tests, while others do not (Abaraogu, Duru & Setchell forthcoming; Setchell, Watson, Jones, Gard & Briffa, 2014). Further attempts to explain stigma include the personality trait approaches associated primarily with Adorno, Frenkel-Brunswick, Levinson, and Sanford (1950).…”
Section: Stigmamentioning
confidence: 99%
See 1 more Smart Citation
“…However, this theory cannot explain why only some people stigmatise. It cannot explain why some physiotherapists score highly on weight stigma tests, while others do not (Abaraogu, Duru & Setchell forthcoming; Setchell, Watson, Jones, Gard & Briffa, 2014). Further attempts to explain stigma include the personality trait approaches associated primarily with Adorno, Frenkel-Brunswick, Levinson, and Sanford (1950).…”
Section: Stigmamentioning
confidence: 99%
“…There is an even smaller amount of research highlighting the claim that physiotherapists also are stigmatised (or self-stigmatise) for possessing various "othered" attributes. For example, physiotherapists hold self-stigmatising fears of gaining weight (Setchell et al, 2014), discipline their own bodies to "maintain a healthy weight" (Black, Marcoux, Stiller, Qu & Gellish, 2012, p. 1424, and negotiate disability stigma (Atkinson, & Owen Hutchinson, 2005). This second body of research, although not the focus of this chapter, highlights that it is important to acknowledge that physiotherapists too can have bodies, behaviours or attributes that may be stigmatised.…”
Section: Physiotherapymentioning
confidence: 99%
“…question the effectiveness of nurses, physicians, dieticians and nutritionists directing the future of obesity treatment and prevention, if these students are unwilling or unable to engage empathically with overweight and obese people. Reviewing wider weight bias research in order to consider other healthcare professionals, Setchell et al (2014) found that Australian physiotherapists demonstrate negative weight bias, especially explicitly, which may potentially negatively affect patients who are overweight or obese physiotherapy treatment. This study was however carried out in Australia thus potentially unrepresentative, and the case study format with freetext response options lacked the sensitivity of examining more subtle forms of discrimination, the nature of these anti-fat attitudes and the manifestations of this weight bias in clinical settings.…”
Section: Weight Bias Within Healthcare Settingsmentioning
confidence: 99%
“…For example, several studies and theoretical investigations (including some of my own) have claimed that physiotherapists inadvertently stigmatize particular characteristics, such as aspects of disability, mental illness, persistent pain, and obesity. [1][2][3][4][5][6][7][8] The authors of some of these investigations have also argued that physiotherapists (again inadvertently) lack an understanding of the stigma people might experience, thereby sometimes creating negative consequences for those they treat. 1,5,6 As a physiotherapist in one of my studies 6 said, ''I haven't thought about how [larger patients] would feel coming to see me.…”
mentioning
confidence: 99%